Challenges of Implementing Merdeka Curriculum in Pancasila Education Subjects in Elementary Schools - Arjun Prasetyo; Anam, Edy Choirul; Rawanoko, Endrise Septina (CAKRAWALA: Journal of Citizenship Teaching and Learning, 2024)
This study aims to identify the challenges faced by teachers in implementing Merdeka Curriculum in Pancasila Education subjects in grade 5 of Al-Islam 2 Elementary School in Jamsaren Surakarta, and formulate solutions to overcome these difficulties. This research uses a qualitative approach with a case study design. The study population consisted of 5th grade students, with a sample of class 5A consisting of 30 students. Data were collected through observation, semi-structured interviews, and literature study. The instruments used include observation sheets that contain aspects of planning, implementation, evaluation, challenges, and learning models. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results showed that teachers experienced the main obstacle in the form of lack of time in implementing learning, which had an impact on not achieving a deep understanding of the material. In addition, student evaluation results are often not in accordance with teacher predictions, both in LOTS (Low Order Thinking Skill) and HOTS (Higher Order Thinking Skill) questions. The proposed solutions include the implementation of more efficient learning models such as flippedclassroom and more structured Project-Based Learning, as well as the use of learning technology to speed up the evaluation process. The study suggests that teachers pay attention to more effective planning time, as well as conducting early diagnostic analysis and reflection on evaluation results to adjust future questions and teaching methods.